First Error-Based Supervised Learning Algorithm for Spiking Neural Networks - Luo, Xiaoling; Qu, Hong; Zhang, Yun; Chen, Yi (Frontiers in Neuroscience, 2019)
Neural circuits respond to multiple sensory stimuli by firing precisely timed spikes. Inspired by this phenomenon, the spike timing based spiking neural networks (SNNs) are proposed to process and memorize the spatiotemporal spike patterns. However, the response speed and accuracy of the existing learning algorithms of SNNs are still lacking compared to human brain. To further improve the performance of learning precisely timed spikes, we propose a new weight updating mechanism which always adjusts the synaptic weights at the first wrong output spike time. The proposed learning algorithm can accurately adjust the synaptic weights that contribute to the membrane potential of desired and non-desired firing time. Experimental results demonstrate that the proposed algorithm shows higher accuracy, better robustness and less computational resources compared with the remote supervised method (ReSuMe) and the Spike Pattern Association Neuron (SPAN) which are classic sequence learning algorithms. In addition, the SNN-based computational model equipped with the proposed learning method achieves a better recognition results in speech recognition task compared with other bio-inspired baseline systems.